Migration, Civil Society and Global Governance - Schierup, Carl-Ulrik; Likić-Brborić, Branka; Delgado Wise, Raúl; Toksöz, Gülay (Rethinking Globalizations, 2019)
ow do the United Nations, international organizations, governments, corporate actors and a wide variety of civil society organizations and regional and global trade unions perceive the root causes of migration, global inequality and options for sustainable development? This is one of the most pertinent political questions of the 21st century. This comprehensive collection examines the development of an emerging global governance on migration with the focus on spaces, roles, strategies and alliance-making of a composite transnational civil society engaged in issues of rights and the protection of migrants and their families. It reveals the need to strengthen networking and convergence among movements that adopt different entry points to the same struggle, from fighting 'managed' migration to contesting corporate control of food and land. The authors examine the opportunities and challenges faced by civil society in its endeavour to promote a rights-based approach within international and intergovernmental fora engaged in setting up a global compact for the management of migration, such as the Global Forum for Migration and Development, and in other global policy spaces.